PENGEMBANGAN MODEL PEMBELAJARAN MEMBACA BERBASIS PERMAINAN BAGI PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR DI KOTA MAKASSAR - Muh. Amin (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2017)
Research development is there stage of design, development, and dissemination. This research data includes expert test result data, practitioner test, and field test result. Data analysis uses qualitative and quantitative description techniques. The objective of the research is to produce the model product of PMBP-PK relating to learning planning (syllabus, RPP, LKS, and teaching materials) and the implementation of learning. The results of the research based on expert and practitioner's test on the feasibility of the content and validation of syllabus content is declared feasible. Percentage of structure effectiveness and syllabus criteria are effective as they reach 79.17%. Expert and practitioner test results on the feasibility and validation of RPP are eligible and valid. Percentage of suitability of structures and criteria reached the level of conformity of 3.68 or 92%. The result of feasibility test of LKS product is feasible based on expert and practitioner validator result. The percentage of conformity of LKS in the appropriate category is 87.5%. Expert and practitioner test results on teaching materials are declared eligible, valid, and appropriate (very suitable) category that is 3.78 or reach 94.5%. The result of the expert assessment of the reading of the game (whispered chain, read do, jumping word sphere, and word of discourse) reached the appropriate category (70.83%) and the practitioner's test result is very effective (97.92%). The results of field trials learning model reading as a whole are in good category. Research findings on PMBP-PK model products, (1) learning planning, implementation of learning, and assessment stated valid, effective, and practical, (2) games in reading learning according to the age level of second grade students of elementary school, and (3) according to the game in learning in positive / good category.